RETRACTED: Curcumin Exerts Effects on the Pathophysiology of Alzheimer’s Disease by Regulating PI(3,5)P2 and Transient Receptor Potential Mucolipin-1 Expression - Zhang, Lu; Fang, Yu; Cheng, Xuan; Lian, Ya-Jun; Xu, Hong-liang; Zeng, Zhao-Shu; Zhu, Hong-can (Frontiers in Neurology, 2017)
Background: To validate our speculation that curcumin may ameliorate Alzheimer’s disease (AD) pathogenesis by regulating PI (3, 5) P2 and TRPML1 expression levels. Methods: We developed an animal model presenting AD by APP/PS1 transgenes. The mouse clonal hippocampal neuronal cell line HT-22 was treated with Aβ1-42. Curcumin was administrated both in vivo and in vitro. MTS assay was used to detect cell viability, and the lysosomal [Ca2+] ion concentration was detected. The number of autophagosomes was detected by the transmission electron microscopic examination. Illumina RNA-seq was used to analyze the different expression patterns between Aβ1-42-treated cells without and with curcumin treatment. The protein level was analyzed by the Western blotting analysis. PI (3, 5) P2 or TRPML1 was knocked down in HT-22 cells or in APP/PS1 transgenic mice. Morris water maze (MWM) and recognition task were performed to trace the cognitive ability. Results: Curcumin increased cell viability, decreased the number of autophagosomes and increased lysosomal Ca2+ levels in Aβ1-42-treated HT-22 cells. Sequencing analysis identified TRPLML1 as the most significantly upregulated gene after curcumin treatment. Western blotting results also showed that TRPML1 was upregulated and mTOR/S6K signaling pathway was activated and markers of the autophagy-lysosomal system were downregulated after curcumin use in Aβ1-42-treated HT-22 cells. Knockdown of PI (3, 5) P2 or TRPML1 increased the protein levels of markers of the autophagy-lysosomal system after curcumin use in Aβ1-42-treated HT-22 cells, inhibited mTOR/S6K signaling pathway, increased the protein levels of markers of the autophagy-lysosomal system after curcumin use in APP/PS1 mice. Besides, knockdown of PI (3, 5) P2 or TRPML1 reversed the protective role of curcumin on memory and recognition impairments in mice with APP/PS1 transgenes, Conclusion: To some extent, it suggested that the effects of curcumin on AD pathogenesis were, at least partially, associated with PI (3, 5) P2 andTRPML1 expression levels.